Januíbe Tejera: music and scene from the perspective of a composer and conductor (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
In an interview given in November 2022, Januíbe Tejera recounts his trajectory in musical composition and conducting, his processes and learning in experimentations as a stage director, bringing the perspective of composition and conducting as directional elements for the show. He comments on his trajectory and support received in the family path, academic of music at UDESC, director of a festival in Porto Alegre, composer and director of shows at the conservatory in France and the initial works as professor of music and scene in an institution in the United States.
Keywords: music and scene; composition and conducting; scene direction